Exploring the Impact of Artistic Expression on Children's Emotional Well-being: A Review - Samridhi Kohli; Ishita Thakur; Kashish Sharma; Sangeeta Kakkar (International Journal of Children, 2025)
Aim: The purpose of the review was to focus on how art therapy could improve children's mental health, particularly for those who are dealing with psychological or emotional difficulties. Children can communicate feelings and experiences that they might find difficult to express verbally via art therapy, a type of therapy that makes use of artistic expression. The review explores developmental ideas, including Malaguzzi's Reggio Emilia method, which encourages self-expression via art, and Lowenfeld's focus on creativity in child development. In particular, it evaluates how art therapy might help kids manage behavioural problems, anxiety, and trauma while enhancing their emotional resilience and behaviour. Methodology: A qualitative methodology was used the review paper by combining the results of previous research of ten years on art therapy and children's mental health. Primary databases such as peer-reviewed publications, case studies, and theoretical literature on developmental psychology and art therapy were included. The analysis examines their distinct contributions to improving emotional control and mental well-being using a range of artistic mediums,. There are case studies used to show how certain artistic treatments may improve children's behavioural outcomes and coping skills. Results: The results highlight how important art is for fostering emotional development, advancing mental health, and giving kids a better sense of who they are. Conclusion: In the end, this study promotes more studies on the long-term advantages of art therapy in educational and therapeutic contexts, especially for kids with complex emotional needs. This review paper attempts to give a thorough overview of the therapeutic potential of creative expression for children by comparing theoretical viewpoints and case studies.
Keywords: Art- therapy; Mental health; creative expression; distress; holistic development